Hypotensive and diuretic activities of aqueous-ethanol extract of Asphodelus tenuifolius (Bangladesh Journal of Pharmacology, 2016)
In order to rationalize the traditional uses of Asphodelus tenuifolius in cardiovascular complaints, aqueous-ethanol extract of the plant was investigated for hypotensive and diuretic activities using in vivo and in vitro models. Intravenous administration of the extract in anesthetized rats produced 14.5 (95% CI; 13.315.6), 24.5 (95% CI; 21.3-27.9) and 35.3% (95% CI; 32.042.5)  fall in mean arterial blood pressure at the doses of 3, 10 and 30 mg/kg, respectively. The extract increased the urine volume and electrolytes excretion significantly at the doses of 300 and 500 mg/kg in rats. In rabbits isolated aorta preparations, the extract, like verapamil, relaxed K+ (80 mM)-induced contractions more potently than phenylephrine (1 µM)induced contractions, indicating Ca2+ antagonistic activity. The extract produced dose-dependent stimulant followed by depressant effects in spontaneously contracting rabbits paired atria preparations. The results suggest that the extract of A. tenuifolius has hypotensive and diuretic effects in animals.Video Clip of Methodology:Hypotensive activity in anesthetized rats: 7 min 25 sec   Full Screen   Alternative